[3 + 3] Cycloaddition of aza-oxyallyl cations with 1, 4-dithiane-2, 5-diols for the construction of 3-thiomorpholinones. Issue 9 (2nd May 2020) - Xie, Lei; Guo, Sheng-nan; Wu, Ping; Gao, Zhenzhen; Liu, Fang; Yuan, Chunhao
Abstract: Base-mediated [3 + 3] cycloaddition reaction of in-situ formed aza-oxyallyl cations and 1, 4-dithiane-2, 5-diols has been achieved under mild reaction conditions. This strategy provides direct and efficient access to prepare desired thiomorpholin-3-one derivatives in moderate-to-high yields. The approach features broad substrates scope and short reaction time. Moreover, the resulting products can be readily converted into other useful heterocyclic compounds including 2 H -1, 4-thiazin-3(4 H )-ones and thiomorpholine-3, 5-diones. Graphical Abstract: